Writing on the Wall. - Patel, Samir S. (Archaeology)
The article reports on the Graffiti Archaeology Project. The website, created by Cassidy Curtis, records the work done on graffiti walls in San Francisco and Los Angeles, California and New York City. Curtis wanted to record the constantly changing art he saw on the walls. His site allows visitors to peel back the layers of paint and overlay current images on older ones.